(untitled) (Journal of the College of Basic Education, 2022)
The place represents an important narrative element, as it occupies an important position that cannot be bypassed, as it formed a network of link with other narrative elements, so the modern narrative work constitutes the disclosure of narrative concepts and how to elicit these concepts through narrative works . In this research, we will stop at the linguistic concept of the place and the idiomatic, then we will review the importance of the place in the narrative work and stand at the types of places.